A New Wideband Circularly Polarized Dielectric Resonator Antenna Loaded with Strips. (5th July 2021) - Hao, Lichao; Wang, Hao; Li, Bo; Yin, Wenting
Abstract : This paper proposes a novel wideband circularly polarized (CP) dielectric resonator antenna (DRA) loaded with strips. The CP DRA comprises a circular DR, two pairs of driven L-like DR strips with different lengths, and a square ground-plane. To couple the electromagnetic energy to circular DR, an orthogonal cross-slot is used, and a stepped microstrip-line is also used to adjust the impedance matching. Influenced by the concept of deformed DR, two pairs of L-like DR strips of different lengths are inserted into the circular DR as part of the driven element to excite a new axial ratio (AR) resonant point. An antenna prototype is simulated, manufactured, and measured to validate the unique design. The measured results show that the designed antenna has broadband characteristic with a −10 dB IBW of 54% (1.91–3.32 GHz) and 3 dB ARBW of 42.1% (2.10–3.22 GHz).